2017
DOI: 10.1007/s12253-017-0288-1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Hu-Antigen Receptor (HuR) Expression is Associated with Tumor Aggressiveness and Poor Prognosis but not with COX-2 Expression in Invasive Breast Carcinoma Patients

Abstract: Hu-antigen R (HuR), a RNA-binding protein, is considered to play a crucial role in tumor development and progression by stabilizing or regulating a group of cellular mRNAs of cancer-related genes, such as cyclooxygenase-2 (COX-2). The present study aimed to evaluate the clinical significance of HuR and COX-2 expression in invasive breast carcinoma. HuR and COX-2 protein expression was assessed immunohistochemically on paraffin-embedded breast cancer tissue sections obtained from 121 patients and was statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…Indeed, the histological evaluation shows that in nonmalignant (normal) tissue, HuR is predominantly found in the nucleus, whereas in cancerous tumors, HuR is cytoplasmic (Stoppoloni et al, 2008; J. Wang et al, 2009). This increase in cytoplasmic HuR also strongly correlates with higher tumor grade and poorer patient outcomes (Giaginis et al, 2017), including worse prognosis (Stoppoloni et al, 2008; J. Wang et al, 2009). Our data show that there is a notable increase in cytoplasmic HuR in vimentin‐positive cells from IPF lung compared to the largely nuclear HuR in control (nonfibrotic) lung.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the histological evaluation shows that in nonmalignant (normal) tissue, HuR is predominantly found in the nucleus, whereas in cancerous tumors, HuR is cytoplasmic (Stoppoloni et al, 2008; J. Wang et al, 2009). This increase in cytoplasmic HuR also strongly correlates with higher tumor grade and poorer patient outcomes (Giaginis et al, 2017), including worse prognosis (Stoppoloni et al, 2008; J. Wang et al, 2009). Our data show that there is a notable increase in cytoplasmic HuR in vimentin‐positive cells from IPF lung compared to the largely nuclear HuR in control (nonfibrotic) lung.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that myofibroblasts from patients with IPF have increased protein translation, especially from messenger RNA (mRNA) that encodes ECM (Larsson et al, 2008). Although the importance of posttranscriptional events in the context of pulmonary fibrosis remains largely unknown, several RNA binding proteins, including human antigen R (HuR), have been shown to play an important role in the etiology of several human pathologies (Giaginis et al, 2017). HuR is a member of the Hu/embryonic lethal, abnormal vision (ELAV) family of RNA binding proteins that is encoded by the ELAVL1 gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HuR has been reported to be associated with numerous human carcinomas, including breast (40), liver (41), pancreatic (42), ovarian (43,44) and colorectal cancer, as well as NScLc (45,46). Recently published studies indicated that elevated HuR expression is associated with aggressiveness and poor prognosis in patients with invasive breast carcinoma and lung carcinoma (47,48). Furthermore, HuR also stabilizes mRNAs encoding crucial regulators of cellular proliferation, differentiation and stress response, such as cyclins (49), cyclooxygenase-2 (50,51), p21 (52), HER2 (53) and Bcl-2 (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…( 71 ) Also, a COX-2 mRNA AU-rich element-binding protein, Hu-antigen R (HuR), has been shown to have a detrimental effect on COX-2 mRNA half-life. ( 72 ) In another study, we prepared sepharose beads, which zerumbone bound to. ( 73 ) A competitive pull-down assay of cell lysate from RAW264.7 mouse macrophages incubated with zerumbone-bound sepharose beads with or without increased concentration of zerumbone was then conducted.…”
Section: Non-specific Protein Binding By Zerumbonementioning
confidence: 99%